Stable isotope analysis of fauna and soils from sites in the Eastern Free State and Western Lesotho, Southern Africa : a palaeoenvironmental interpretation - Smith, Jeannette (Department of Archaeology, 2016)
This thesis examines the use of stable carbon isotopes as a means of reconstructing the palaeoenvironment of the Caledon River Valley of the eastern Free State, South Africa, and western Lesotho. In doing so, this work draws upon previous studies that have shown that the distinct distribution and δ¹³C values of C₃ and C₄ grasses are influenced by seasonality of rainfall and growth season temperatures. In general, C₃ grasses dominate in areas where conditions are cool/moist during the growth season, while C₄ grasses characterize those that are warm/arid. The isotopic composition of the grasses of an area, and thus climatic and environmental data, is passed along the trophic levels, through dietary intake by grazers, and decomposition into soil sediments. By measuring the ¹³C/¹²C ratios of carbon extracted from the calcified tissues of grazers and soil organic matter recovered from within an archaeological context, a palaeoenvironmental sequence has been reconstructed for the study area for the last 13 500 years. Results have shown that although C₄ grasses have dominated, the presence of C₃ grasses, at various times during this period, suggest that growth season temperatures fluctuated temporally and spatially.